Risk factors for early mortality on antiretroviral therapy in advanced HIV-infected adults. (23rd October 2017) - Bisson, Gregory P.; Ramchandani, Ritesh; Miyahara, Sachiko; Mngqibisa, Rosie; Matoga, Mitch; Ngongondo, McNeil; Samaneka, Wadzanai; Koech, Lucy; Naidoo, Kogieleum; Rassool, Mohammed; Kirui, Fredrick; Banda, Peter; et al.
Abstract : Background: Many HIV-infected individuals present with advanced HIV disease. These patients are at high risk of death after antiretroviral therapy (ART) initiation, but risk factors for death in these patients are unclear. Methods: We used data from a multisite randomized trial comparing empiric vs. preventive tuberculosis therapy in HIV-infected adults initiating ART with CD4 + T-cell counts less than 50 cells/μl to evaluate risk factors for death within 48 weeks after ART initiation. Cox proportional hazards models were fit to evaluate characteristics present at baseline and at 4 weeks after ART initiation, including the week 4 CD4 + T-cell response and new opportunistic infections. Results: Of 850 enrolled, the median pre-ART CD4 + T-cell count was 18 cells/μl and 67 (7.9%) died. Baseline risk factors for death included lymphadenopathy, lower CD4 + T-cell count, lower serum albumin, high white blood cell count, elevated neutrophil percentage, and lower hemoglobin. Among 746 participants with data at week 4, the median changes in CD4 + T-cell count and viral load for those who died ( n = 43) vs. survived were 26 vs. 56 cells/μl and −2.7 vs. −2.7 log10 copies/ml, respectively. Each 20 cell/μl lower change in week 4 CD4 + T-cell count was associated with a 20% increased risk of post week-4 mortality (adjusted hazard ratio 1.20, 1.01–1.42, P = .038). Conclusion: Evidence of active infection and suboptimal immunologic response during the first month of ART are associated with death in the first year after ART initiation in those with advanced HIV disease taking tuberculosis preventive therapy. Strategies to reduce early mortality in this population warrant further investigation. Abstract : Supplemental Digital Content is available in the text